Efektivitas Program Fisioterapi pada Pasien Pasca Spondilitis Tuberkulosis di Rumah Sakit Paru Ario Wirawan Salatiga: (Studi Kasus) - Fadhil Kusuma Ningrum; Isnaini Herawati; Ririt Ika Lestari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
This case report examines the effectiveness of a combined pulmonary rehabilitation and musculoskeletal physiotherapy program for a 26-year-old male post-pulmonary tuberculosis patient with lumbar tuberculous spondylitis. The patient, who had completed anti-tuberculosis treatment, presented with low back pain, shortness of breath, fatigue, and limited mobility. Spirometry indicated severe restrictive ventilatory impairment (FVC 1.28 L, 32% of predicted), and lower extremity muscle strength was reduced (MMT 2-3/5). The patient used a TLSO brace and walking aid. Over a three-week physiotherapy program, the patient participated in breathing exercises, spinal mobilization, muscle strengthening, functional exercises, and education on brace use. Evaluation occurred at the first, second, and third weeks. After treatment, pain intensity decreased from VAS 6 to VAS 3, FVC improved to 1.72 L, chest expansion increased, muscle strength improved to MMT 4/5, and performance on the Five-Times Sit-to-Stand Test showed progress. The Functional Independence Measure (FIM) score increased from 98 to 115, reflecting improved functional independence. These findings suggest that the combination of pulmonary and musculoskeletal physiotherapy effectively improved respiratory function, muscle strength, and the patient’s overall functional capacity.